Prenatal characterization of a novel inverted SMAD2 duplication by mate pair sequencing in a fetus with dextrocardia. Issue 2 (10th December 2020) - Zepeda‐Mendoza, Cinthya J.; Essendrup, Anna; Smoley, Stephanie A.; Johnson, Sarah H.; Hoppman, Nicole L; Vasmatzis, George; Jackson, Daniel L.; Kearney, Hutton M.; Baughn, Linda B.
Abstract: This case report underlines the importance of molecular characterization of genomic duplications and other structural variants in the prenatal setting to guide clinical interpretation, genetic counseling, and perinatal medical care. Abstract : This case report underlines the importance of molecular characterization of genomic duplications and other structural variants in the prenatal setting to guide clinical interpretation, genetic counseling, and perinatal medical care.